Histological Study of Respiratory Organ of Betta sp. - Apriliani, Nurul Safitri; Supriyati, Hikmah; Luthfi, Muhammad Ja’far (Proceeding International Conference on Science and Engineering, 2019)
Betta sp. is a freshwater ornamental fish which also known as a fighting fish. One of the fundamental organs to support fishes life is respiratory organ. Fighting fish is belongs to the suborder Anabantoidei which means labyrinth fishes group. The aim of the study was to know histology of the respiratory organs of Betta sp. Histological preparations were done using paraffin method, stained with Hematoxylin-Eosin (HE). The result showed that Betta sp. has a respiratory organ common fish i.e gills and additional respiratory organ structure namely labyrinth and pseudobranch that makes Betta sp can survive in a low volume of water. The gill is consists of gill arch, gill raker, gill fillament and gill lamellae. The labyrinth is consist of connective tissue and folded ephitelium. Pseudobranch according to some literature function as an additional respiratory. Functions attributed to the pseudobranch include; regulation of oxygen to the eyes, enzyme production for use in the gas bladder, osmoregulation, and many others.